On the evaluation of methods for the recovery of plant root systems from X-ray computed tomography images - Mairhofer, Stefan; Sturrock, Craig; Wells, Darren M.; Bennett, Malcolm J.; Mooney, Sacha J.; Pridmore, Tony (CSIRO Publishing, 2014)
X-ray micro computed tomography (µCT) allows non-destructive visualisation of plant root systems within their soil environment and thus offers an alternative to commonly used destructive methodologies for the examination of plant roots and their interaction with the surrounding soil. Various methods for the recovery of root system information from X-ray CT image data have been presented in the literature. Detailed, ideally quantitative, evaluation is essential, in order to determine the accuracy and limitations of the proposed methods, and to allow potential users to make informed choices between them. This, however, is a complicated task. Three-dimensional ground truth data is expensive to produce, and the complexity of X-ray CT data means that manually generated ground truth may not be definitive. Similarly, artificially generated data is not entirely representative of real samples. The aims of this work are to raise awareness of the evaluation problem and to propose experimental approaches that allow the performance of root extraction methods to be assessed, ultimately improving the techniques available. To illustrate the issues, tests are conducted using both artificially generated images and real data samples.